Monosaccharide production in an acid sulfite process: Kinetic modeling. (13th February 2015) - Rueda, C.; Fernández-Rodríguez, J.; Ruiz, G.; Llano, T.; Coz, A.
Highlights: The hydrolysis of wood by means of acid sulfite process has been studied. A kinetic modeling of sugar and inhibitors evolution has been done. Acetic acid from acetyl groups, sugar and decomposition products have been modeled. Kinetic orders of more than one have been obtained for sugar and inhibitors. The model permits the study of sugar evolution in spent liquor for its valorization. Abstract: Spent sulfite liquor is a lignocellulosic waste obtained after the sulfite pulping process. It is mainly formed by sugars and lignosulfonates which are isolated from the pulp during the cooking process. The current work investigates the kinetic modeling of the sulfite process from a biorefinery point of view since monosaccharides present in the spent liquor can be used as a raw material in further biorefinery processes to produce other value-added products. Kinetic parameters of carbohydrate degradation have been determined following sugar and inhibitors from wood to spent liquor, using laboratory scale reactors and different temperatures, 130, 140 and 150 °C. Three types of reaction schemes were developed. Kinetic parameters were obtained for each one using first and n order reactions, using Aspen Custom Modeler. Results show that the best temperature to be used in the process is 130 °C, giving the maximum sugar conversion, 33.91 mol% and obtaining 13.81 mol% of decomposition products.